Hasil Belajar dan Aktivitas Siswa Setelah Diterapkan Pembelajaran Guided Inquiry Pada Materi Penerapan Listrik DC dan AC - Sugiarti Sugiarti (SEJ (Science Education Journal), 2017)
This study aims to determine the results of student learning after applied physics learning using guided inquiry model and student activities during the process of physics-based learning guided inquiry in high school on the material Application of AC and DC Power. Implementation of this learning using one group pretest-posttest design, the first step to make measurements as the initial test, then subject to treatment within a certain time, then performed the final test. After doing teaching and learning activities on the material application of DC electricity and AC classical completeness reached 91.7%. The average student learning outcomes after guided inquiry based learning activities increased from 34.2 to 85. The most frequent student activity in the guided inquiry learning phase was experimentation and listening to teacher's explanation of 14%.